Confronting the nation's water problems : the role of research (National Academies Press, 2004)
In order to confront the increasingly severe water problems faced by all parts of the country, the United States needs to make a new commitment to research on water resources. A new mechanism is needed to coordinate water research currently fragmented among nearly 20 federal agencies. Given the competition for water among farmers, communities, aquatic ecosystems and other users--as well as emerging challenges such as climate change and the threat of waterborne diseases--Confronting the Nation's Water Problems concludes that an additional $70 million in federal funding should go annually to water research. Funding should go specifically to the areas of water demand and use, water supply augmentation, and other institutional research topics. The book notes that overall federal funding for water research has been stagnant in real terms for the past 30 years and that the portion dedicated to research on water use and social science topics has declined considerably.